(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
Biblionline Vol. 10, n. 1 (2014) Link de acesso ao número http://periodicos.ufpb.br/ojs2/index.php/biblio/issue/view/1434/showToc